An Analysis of Mobile Dictionaries in Vocabulary Teaching - Masykur, Masykur (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2017)
In recent years, rapid developments in technology have placed books and notebooks into the mobile phones and tablets and also the dictionaries into these small boxes. Giant dictionaries, which we once barely managed to carry, have been replaced by mobile dictionaries through which we can reach any words we want with only few touches.  Mobile dictionaries with their audiovisual contents have become an important source for vocabulary teaching. Further studies are needed to use this source in a more efficient way and to benefit from it more effectively.  Starting from this point, this study elaborates on the use of mobile dictionaries in vocabulary teaching. In the first place, advantages and the limits of the use of these dictionaries in vocabulary teaching are tried to be determined students viewpoint to them and how frequently they are used. In light of the emerging data, new ways are sought to use these dictionaries as a more efficient teaching material. For this purpose, a survey was conducted to seventy-eight students of Wiralodra University Indramayu in 2016 -2017 academic year. A survey form was prepared by receiving opinion of an expert and reviewing related literature. Descriptive statistic techniques were used in the analysis of data gathered. At the end of the study, almost all students expressed that they were constantly using mobile dictionaries to learn vocabulary. Besides, students put forth the advantages and limits of them. We hope this study will make contribution to studies regarding more efficient way to use of these dictionaries in vocabulary teaching.  Keywords: Mobile dictionaries, vocabulary teaching, dictionary applications